Penerapan Sistem Menu Engineering dalam Upaya Peningkatan Kualitas Menu di Restoran Bintan Inti Executive Village Clubhouse - Adiguna Tumpuan (Sekolah Vokasi, Universitas Gadjah Mada, 2021)
This research is a form of analysis and evaluation of the menu at the Bintan Inti Executive Village (BIEV) Clubhouse through a menu engineering system with the aim of improving the quality and effectiveness of the menu served. The formulation of the problem which is the basis of this research is how to improve the quality of the food and beverage menu through the menu engineering system and what recommendation actions should be taken based on the resulting data from the analysis that appears. This study uses variables, which are menu analysis in improving the quality of the menu at BIEV Clubhouse with sub variables, such as food cost, menu mix, and contribution margin. The results of this study that there were 8 menus or 30.77% menus with star categories, 5 menus or 19.23% menus with the plowhorse category, 4 menus or 15.38% menus with the puzzle category, and 9 menus or 34.62%. menu with dog category. The recommended follow-up actions to BIEV Clubhouse management is reducing the menu with the dog category, evaluating product prices and production costs for menus with the plowhorse category, taking suggestive selling steps for menus with the puzzle category, and maintaining the quality and performance of menus with the star category.